CFD evaluation of the pottery water fall in hot arid climate of Luxor, Egypt - Ismail, Moustafa Anwar Moustafa Mohamed (Kulliyyah of Architecture and Environment Design, International Islamic University Malaysia, 2013)
The research is an attempt to improve the existing water wall by means of experimenting the humidity and temperature levels improvement caused by the pottery water wall. This study aims to evaluate the pottery water wall in hot arid climate specifically Luxor, Egypt using ANSYS Fluent for Computational Fluid Dynamics CFD simulation. The pottery water wall is a passive system in which the concept has been patented by the author at the Egyptian Patent Office. The pottery water wall is a combination of a water wall and porous ceramic pipes for evaporative cooling. It is regarded as an improvised version of the water wall. The study evaluates the efficiency of the pottery water wall in cooling and heating. The study compares between its designs, aiming to decipher the most efficient design of the pottery water wall, by simulating four different models on a room with a volume of 75m3 with three different opening sizes, porous ceramic pipes and surface areas as variances. The most efficient model of the pottery water wall derived from the first simulation will be evaluated for thermal comfort in the worst climatic conditions in Luxor, Egypt. The findings showed that the highest efficiency of the pottery water wall was achieved while using a moderate sized opening (900mm x 900mm), while its efficiency decreases if the opening size of 900mm by 900mm is made smaller or bigger. The simulation findings found that the pottery water wall can help to cool the room by decreasing its indoor air temperature between 4oC and 10oC and heat the room by increasing its temperature between 4oC and 15oC. The decrease and increase in temperature depends on the efficiency of the pottery water wall and its design. The simulation results indicated that the pottery water wall achieved comfortable indoor temperature for 62.5% of the 21st of June 2011 the day resembling extreme summer, achieved thermal comfort for 62.5% of the 21st of January 2012 the day resembling extreme winter and 75% of an average day (21st of April 2012). Based on the simulation results, it can be deduced that an appropriate design of the pottery water wall can cut down the cooling and heating demand by 88% in the extreme climatic conditions of Luxor, Egypt both in summer and winter.